OBSERVAÇÕES SOBRE A POLINIZAÇÃO DE MELÃO (Cucumis melo L.) CULTIVADO EM ESTUFA - Marchini, Luis Carlos; Almeida, Daniela de; Vásquez, M. A. N.; Moreti, Augusta C. de C. C.; Otsuk, Ivani Pozar (REVISTA DE AGRICULTURA, 2015)
OBSERVAÇÕES SOBRE A POLINIZAÇÃO DE MELÃO (Cucumis melo L.) CULTIVADO EM ESTUFA